La Santa Muerte in Mexico : History, Devotion, and Society - Pansters, W. G. (Wil G.) (Book collections on Project MUSE., 2019)
This book examines La Santa Muerte's role in people's daily lives and explores how popular religious practices of worship and devotion developed around a figure often associated with illicit activities.